The Satellite Risk Prediction and Radiation Forecast System (SaRIF). Issue 12 (14th December 2021) - Horne, Richard B.; Glauert, Sarah A.; Kirsch, Peter; Heynderickx, Daniel; Bingham, Suzy; Thorn, Peter; Curran, Babara‐Ann; Pitchford, David; Haggarty, Ewan; Wade, David; Keil, Ralf
Abstract: With new satellite constellations being launched into low Earth orbit, the growing use of medium Earth orbit for radio‐navigation and timing signals, slot region orbits for telecommunications and the introduction of electric propulsion to reach geostationary orbit, there is a growing need to develop services to protect satellites from space weather. Here we highlight two recent events in relation to satellite operations. We summarize 10 user needs that arose out of meetings with satellite operators, designers, underwriters and space agency staff. We present the satellite risk prediction and radiation forecast (SaRIF) system which is designed to meet most of these needs. The system uses real‐time data as input to the BAS radiation belt model (BAS‐RBM) to solve the Fokker Planck equation and provides a forecast of the electron flux throughout the outer radiation belt with 1‐hr resolution up to 24 hr ahead. The electron flux is used to calculate charging currents, and is combined with GOES near real time proton fluxes to calculate dose rate and total ionizing dose behind set levels of shielding for satellites in Medium Earth orbit, Geostationary orbit and slot region orbits. The results are compared against design standards and presented as risk indicators to forecast the risk of damage. The system works automatically and is updated every hour. We also present data and a best reconstruction of the radiation environment which are held in a searchable archive for satellite anomaly resolution. The SaRIF system is available via the European Space Agency space weather web portal. Plain Language Summary: With new satellite constellations being launched into low Earth orbit, the growing use of other orbits and the introduction of electric propulsion, we need to protect satellites from space weather. Here we highlight two recent events in relation to satellite operations. We summarize 10 user needs that arose out of meetings with satellite operators, designers, underwriters and space agency staff. We present the satellite risk prediction and radiation forecast (SaRIF) system which is designed to meet most of these needs. The system uses real‐time data as input to the BAS radiation belt model (BAS‐RBM) and provides a forecast of the electron flux throughout the outer radiation belt with 1‐hr resolution up to 24 hr ahead. The electron flux is used to calculate charging currents, and is combined with GOES near real time proton fluxes to calculate dose rate and total ionizing dose behind set levels of shielding for satellites on orbit. The results are compared against design standards and presented as risk indicators to forecast the risk of damage. The system works automatically and is updated every hour. We also present a best reconstruction of the radiation environment which are held in a searchable archive for satellite anomaly resolution. Key Points: The satellite risk prediction and radiation forecast (SaRIF) system forecasts the outer electron radiation up to 24 hr ahead, updated every hour Risk indicators are provided for four satellite orbits and can be compared against design standards The SaRIF system provides a searchable archive of data for anomaly resolution by satellite operators, designers and underwriters